(untitled) (African Journal of Biomedical Research, 2022)
The antiplasmodial activity of hexane, ethyl acetate, and methanolic leaf extracts of Clerodendrum violaceum were tested in vitro using Plasmodium falciparum W2 strain blood parasites. HepG2 A16 hepatoma cells were used in the cytotoxicity experiments. Chloroquine-sensitive Plasmodium berghei NK 65-infected mice were examined for suppressive and curative efficacy. Seven (7) groups of five mice were employed for each extract: groups 1-5 were given 31.25, 62.5, 125, 250, and 500 mg/Kg body weight of the various extracts. Animals in group 6 were given 20 mg/kg body weight of chloroquine, whereas those in group 7 were given an identical volume of 5% DMSO as a control (the vehicle used in dissolving the extracts). The drug and extracts were orally administered for four consecutive days. The different extracts were inactive in vitro and did not exhibit any toxicity against HepG2 cells in vitro. They did, however, provide some chemo-suppression in vivo; and the methanolic extract had the best antimalarial efficacy in vivo. In addition, the extracts increased the mean survival time of treated mice when compared to the control group. The findings of this study revealed that Clerodendrum violaceum leaf extracts exhibit antimalarial activity in vivo. As a result, it may be concluded that Clerodendrum violaceum leaves, particularly the methanolic extract, have promising antimalarial potential but may be hazardous in high dosages.